Impact of integrated nutrient management on yield and yield attributes of kharif black gram in submontane zone of Punjab, India - SHARMA, SEEMA; SINGH, JAGDISH (Journal of Soil and Water Conservation, 2024)
A field experiment was conducted to assess the impact of integrated nutrient management on yield and yield attributes of kharif mash. The eight integrated nutrient management treatments viz., T1: Control, T2: Recommended dose of NP (Drill at sowing, 12.5 kg of N ha-1, along with 25 kg P2O5 ha-1) (RDF), T3: 1.25 t ha-1 farm yard manure (FYM)+1/4 th RDF, T4: 2.5 t ha-1 FYM+1/4th RDF, T5: 3.75t ha-1 FYM+ 1/4th RDF, T6: 1.25 t ha-1 pressmud +1/4 th RDF, T7: 2.5 t ha-1 pressmud+1/4th RDF and T8: 3.75 t ha-1 pressmud + 1/4 th RDF were arranged in randomized block design with three replications. The highest grain yield was recorded in T4 treatment where combined application of organic and inorganic fertilizers (FYM @ 2.5 t ha-1 + ¼ th RDF), resulted in significant increase of 30.1 per cent over the control. The number of fruit bearing branches, seeds per pod and pods per plant were significantly higher with T4 treatment compared to control. Among the organic sources combined application of pressmud along with inorganic fertilizers (Pressmud @ 2.5 t ha-1 + ¼ th RDF) also resulted in significant increase of 12.6 percent in grain yield over control. The results revealed significant decrease in soil bulk density and improvement in soil organic carbon with the application of farm yard manure and sugarmill bu-product pressmud in combination with inorganic fertilizers.